A new performance trade-off measurement technique for evaluating image watermarking schemes - Emami, Mir Shahriar (Springer, 2011)
In digital watermarking performance evaluation at least three major metrics: imperceptibility, robustness and capacity have been widely used by researchers to analyze the performance of watermarking schemes; however, they constantly conflict with each other. In this paper we propose an effective method to evaluate the trade-off balanced degree among these measures using three threshold conditions. These thresholds comprise of three factors: imperceptibility effect ‘before attack and after watermarking’, perceptibility effect ‘after attack’, and robustness ‘after attack’. As a result of this study, the performance trade-off of a watermarking scheme can be stated based on degrees. Moreover, we proposed Reset Removal Attack as a severe geometric attack. Finally, the experimental investigation of the proposed technique using the bit-plane watermarking algorithms under several intensities of Reset Removal Attack revealed that the 3rd bit-plane algorithm behaved a better compromise among robustness, image quality, and capacity.